Modelo conceitual para o processo de desenvolvimento de produto têxtil - Rodrigues, Ronaldo dos Santos (2016)
Although the textile industry is significant in the Brazilian industrial context, it’s product development is still dependent on experts who work with particular of methodology or documentation. This leads to rework, delayed release and dependency on specific professionals, making the process vulnerable. This research aims at presenting the conceptual model of a textile product development process, involving the phases of informational and conceptual design, detailed design and preparation for production. The study presents a literature review about the textile industry and its segments, models for industrial product development and the development approaches from the textile industries. Then, in order to develop the aimed model, several methodological proposals for textile development were analyzed, considering some cases studies published and nine industrial fields examined. The survey with the companies was conducted through questionnaires and field studies, aiming to understand the practice of product development in the textile industry. These studies were compared with each other and with the theoretical models, delimiting the original contribution of this research project. To validate the concept of the proposed model, an intervention was carried out in an industry and in the end the performance improvement of the product development process was verified. Among the results, this work presents a conceptual model of product development that supports all necessary stages for industrial practice, focusing on the textile sector.